The Neotropical genera Guadana Rheims, 2010 and Sparianthina Banks, 1929 (Araneae: Sparassidae: Heteropodinae) - Rheims, Cristina A. (Zootaxa, 2021)
The Neotropical genera Guadana Rheims, 2010a and Sparianthina Banks, 1929 are revised. Based on re-interpreted and newly observed characters, updated diagnoses are given for each genus. Eight new species are described, six in Guadana: G. alpahuayo sp. n. (♂♀) and G. ucayali sp. n. (♂), from Peru; G. amendoim sp. n. (♀), G. mapia sp. n. and G. muirpinima sp. n. (♀), from Brazil; G. arawak sp. n. (♂), from French Guiana, and two in Sparianthina: S. boyaca sp. n. (♀) from Colombia and S. soca sp. n. from Trinidad & Tobago. Sparianthina rufescens (Mello-Leitão, 1940) is considered incertae sedis. All new species are illustrated and photographed. Identification keys for both genera including comparative detailed illustrations of male and female characters, as well as updated distribution maps for all known species are provided.